Virtual Device for Calculating Parameters of Epitaxial Layers in the Cultivation of Heterostructures - Suchoruchenkov, Kirill; Maraeva, Evgenia; Alexandrova, Olga (Computer Tools in Education, 2023)
The work is devoted to the creation of a program that allows one to simulate the process of epitaxy and cultivation of semiconductor monocrystals depending on technological parameters. The process of directed growth of one crystal on the surface of another is considered. The term “directed growth” implies that in the presence of a large number of origin centers and their further coalescence (the process of fusion of particles inside the mobile medium (liquid, gas) or on the surface of the body) the emerging epitaxial layer will be monocrystalline, that allows you to specify the planes and directions in the substrate and epitaxial layer, equally oriented in space. The virtual device is intended for use by students and teachers in distance learning and in full-time mode.